Peran Tangible Asset, Capital Expenditure, dan Net Working Capital terhadap Cash Holding Perusahaan Barang Konsumsi di BEI 2020-2022 - Dewi Nugraheni; Noer Sasongko (Forum Kerjasama Pendidikan Tinggi (FKPT), 2026)
This study aims to determine tangible assets, capital expenditure, and net working capital on cash holding. The method used in this study is a quantitative method. The population in this study is consumer goods companies where sampling uses the purposive sampling method, with a sample size of 183 companies. The data analysis technique uses a multiple linear regression model with the help of SPSS software version 25. The results of this study indicate that tangible assets and capital expenditure do not affect cash holding, while net working capital affects cash holding.